Implementing Google Sites to Improve Elementary School Students' Understanding of Science Concepts - Humaira Silfiani; Bunga Syafiq Munira; Vivin Ardiyanti; Dwi Novita Sari; Futry Ayu Lestari (Institut Agama Islam Negeri (IAIN) Curup, 2025)
The lack of Students’ comprehension of scientific topics science classrooms at Madrasah Ibtidaiyah possess underscoring the necessity for effective digital media. This study examines the application of Google Sites as a digital instrument designed to improve fifth-grade students' understanding of scientific ideas. The research utilizes a descriptive qualitative methodology, employing a case study approach that encompasses observation, interviews, and documentation. The informants and data sources for this research are fifth-grade students and teachers at one of the Madrasah Ibtidaiyah in Lhokseumawe city. The research results indicate that implementing the Google Sites learning media can improve students' understanding of science concepts. Students are more enthusiastic about learning, more active, and more responsive, making the learning process more conducive and improving the quality of student learning. Regarding the material on changes of state, students receive more support and have a more profound understanding of the topic presented. Research demonstrates that using Google Sites improves elementary school students' comprehension of science content. The improvement is evident from the students' average score, which increased to 84, 5 students achieving perfect scores (100), and most students score are getting above 80. Thus, the learning process becomes more active and meaningful for students. This research also makes a new contribution, which is the application of easy-to-use, creative, and interactive digital media, thus supporting the quality of science learning in elementary schools.